Whatever Happened to the Canaanites? Principles of a Christian Ethic of Mass Immigration - Biggar, Nigel (Studies in Christian ethics, 2022)
This article aims to articulate a set of general principles of a Christian ethic of mass immigration. Toward this end, it considers: biblical and theological grounds for cosmopolitanism (and ‘open borders’); biblical and theological caveats against cosmopolitanism; elements of a Christian ethic of the treatment of near and distant neighbours; what Francisco de Vitoria’s ‘On the American Indians’ has to contribute; what lessons should be learned from the history of European colonialism; and the nature of mass immigration into twenty-first-century Europe and the problems it entails. The article concludes with six principles: relevant empirical data should be mastered before developing a judgement; concerns about mass immigration should not be dismissed out of hand as ‘racist’; care of the alien may take a variety of forms, not only that of granting asylum; illegal economic immigrants should normally be returned home; compassion should look in several directions—not only at the migrant, but also at the working-class competitor for jobs and services, and at members of government burdened with the responsibility of making hard decisions; and the Christian is obliged to exercise, not only compassion, but justice and prudence.